2019
DOI: 10.1002/mp.13459
|View full text |Cite
|
Sign up to set email alerts
|

In air and in vivo measurement of the leaf open time in tomotherapy using the on‐board detector pulse‐by‐pulse data

Abstract: Purpose We developed an algorithm to measure the leaf open times (LOT) from the on‐board detector (OBD) pulse‐by‐pulse data in tomotherapy. We assessed the feasibility of measuring the LOTs in dynamic jaw mode and validated the algorithm on machine QA and clinical data. Knowledge of the actual LOTs is a basis toward calculating the delivered dose and performing efficient phantom‐less delivery quality assurance (DQA) controls of the multileaf collimator (MLC). In tomotherapy, the quality of the delivered dose d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
(105 reference statements)
1
12
0
Order By: Relevance
“…Again, these results give us a good confidence in the LOT measurement algorithm (see also Ref. [28]). The LOT differences standard deviations (Fig.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Again, these results give us a good confidence in the LOT measurement algorithm (see also Ref. [28]). The LOT differences standard deviations (Fig.…”
Section: Discussionsupporting
confidence: 69%
“…This was extensively investigated in a previous publication. 28 We previously reported that the LOT measurement algorithm works as well in air as in vivo. 28 Thus, the method proposed here would also be valid in vivo.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations